2010
DOI: 10.1073/pnas.1008816107
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial histamine H 1 receptor signaling reduces blood–brain barrier permeability and susceptibility to autoimmune encephalomyelitis

Abstract: Disruption of the blood-brain barrier (BBB) underlies the development of experimental autoimmune encephalomyelitis (EAE) and multiple sclerosis. Environmental factors, such as Bordetella pertussis, are thought to sensitize central endothelium to biogenic amines like histamine, thereby leading to increased BBB permeability. B. pertussis-induced histamine sensitization (Bphs) T he blood-brain barrier (BBB) involves endothelial cells that line the blood vessels of the central nervous system (CNS) and the tight j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 47 publications
1
44
1
Order By: Relevance
“…S1P regulates barrier function, and mice deficient in S1P in plasma were more susceptible to HA-induced vascular leakage (61). Nonetheless, administration of PTX to mice expressing EC-specific H 1 R did not render them sensitive to VAASH (16), which argues against this notion. Taken together, these results did not formally rule out the possibility that Hrh1 on EC is required but suggested that coexpression of H 1 R in another component of the vascular unit may be required for Bphs.…”
Section: Fig 1 Loss Of G␣contrasting
confidence: 44%
See 3 more Smart Citations
“…S1P regulates barrier function, and mice deficient in S1P in plasma were more susceptible to HA-induced vascular leakage (61). Nonetheless, administration of PTX to mice expressing EC-specific H 1 R did not render them sensitive to VAASH (16), which argues against this notion. Taken together, these results did not formally rule out the possibility that Hrh1 on EC is required but suggested that coexpression of H 1 R in another component of the vascular unit may be required for Bphs.…”
Section: Fig 1 Loss Of G␣contrasting
confidence: 44%
“…Using bone marrow chimeras, we found that the nonhematopoietic compartment determined susceptibility to Bphs (16). We found that EC-specific expression of H 1 R was not sufficient to mediate Bphs (16).…”
Section: Fig 1 Loss Of G␣mentioning
confidence: 91%
See 2 more Smart Citations
“…Although the BBB is primarily formed by the endothelium of cerebral capillaries, there are specific interactions and communication at the abluminal side of the BBB with the other cell components of the neurovascular unit (NVU): pericytes, astrocytes, and neurons (Abbott et al, 2010). The local regulation of mediators like neurotransmitters and their movement across these blood-nerve barriers has received relatively little attention, despite the fact that this could influence and terminate receptor-mediated effects on, at least, the integrity and permeability of the brain capillaries of the NVUs (Leybaert, 2005;Lu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%